Early Reading Profile of Slow Learner Students in Inclusive Schools in Yogyakarta - Rezky Ultabaini; Pujaningsih Pujaningsih (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study examines the reading abilities of slow learner students in inclusive elementary schools, focusing on their strengths and weaknesses in accuracy, fluency, vocabulary (receptive and expressive), and comprehension (listening and reading). A quantitative descriptive approach was employed, involving 25 slow learner students (n=25) from inclusive elementary schools in Yogyakarta with IQs ranging from 70 to 88. Data were collected through adapted reading assessment instruments and IQ tests using the Binet and WISC scales. Descriptive statistics were used for analysis. The findings reveal that most slow-learner students were male and were more easily identified at higher grade levels. In lower grades (grades II and III), students demonstrated strengths in receptive vocabulary and listening comprehension but faced challenges with expressive vocabulary, reading accuracy, fluency, and text comprehension. In contrast, higher-grade students (grades IV to VI) showed improvements in receptive and expressive vocabulary and listening comprehension but continued to struggle with reading accuracy, fluency, and comprehension of complex texts. These results underscore the need for targeted interventions. For lower-grade students, enhancing reading accuracy and fluency is crucial, while for higher-grade students, the focus should shift to improving reading comprehension. Early and tailored support is essential to help slow learner students overcome reading barriers and achieve their academic potential, ensuring their inclusion in educational progress.